Unravelling the significance of catalyst reduction stage for high tar reforming activity in the presence of syngas impurities - Dara Khairunnisa Mohamed (2022)
Ni catalysts are used widely in tar reforming for syngas purification. This study investigates the aim of the reduction stage toward Ni catalysts during tar reforming in the presence of syngas impurities. A NiAl2O4 catalyst was used for the reforming of a mixture of tar model compounds (naphthalene, toluene, and styrene) in simulated syngas containing 50 ppmv H2S and 500 ppmv HCl. The catalyst exhibited activity in tar reforming even without the pre-reduction treatment, but it was deactivated rapidly due to the favored reaction between H2S and Ni2+ species, causing increased Ni agglomeration and carbon deposition. Pre-reduction of catalysts enhanced the catalyst stability even in the presence of syngas impurities. Higher reforming activity was achieved by increasing the reduction temperature from 800 °C to 900 °C. However, transformation in the support structure at higher reducing temperature could lead to decreased exposure of Ni due to the collapse of pore structures.